Molecular docking studies on potential PPAR-γ agonist from Rhizophora apiculata (Bangladesh Journal of Pharmacology, 2014)
Peroxisome proliferator-activated receptor gamma (PPAR-γ) agonists are beneficial in the management of diabetes by increasing insulin sensitivity and inhibiting hepatic gluconeogenesis. The aim of the present study was to isolate and evaluate PPAR-γ agonist property of phytocompounds from Rhizophora apiculata using in silico approach. 30 g powdered leaves of R. apiculata extracted through acid-base method and subjected to GC-MS analysis. GC-MS results identified 18 phytocompounds, among those major peaks were 1-adamantyl-p-methylbenzalimine, clivorin, 4-butyl pyridine, 1-oxide, acetamide and p-aminodiethylaniline. In silico analysis of major compounds on human PPAR-γ protein was determined by AutoDock 4.0. Compared to thiazolidinediones, R. apiculata derived ligands acts as a potential agonist with binding energy -4.41, -5.29, -5.28 and -4.27 kcal/mol respectively. The molecular interaction of ligands was at residues of TYR473, ILE326, ARG288, HIS323 and ARG 288 to activate the action of PPAR-γ protein.